2007
DOI: 10.1002/pssc.200673289
|View full text |Cite
|
Sign up to set email alerts
|

The polarizability and the photoionization cross‐section under the external fields for donor impurities in quantum well‐wire

Abstract: PACS 71.55. Eq, 73.21.Hb In this study, we have calculated the donor impurity binding energy, donor impurity related photoionization cross-section and polarizability in symmetricGaAs Ga Al As -quantum well-wire as a function of the impurity positions, dimensions of the structures and external electric and magnetic field, the calculations were performed within the effective mass approximation, using a variational method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Lax 1 was the one who first investigated the photoionization cross-section of hydrogenic impurities in bulk semiconductors. Photon energy depended photoionization cross section has been studied earlier for bulk semiconductors, 2 quantum wells, 3 4 quantum well wires [5][6][7] and quantum dots. 8 9 In all the studies they found that the photoionization cross section depended upon the * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Lax 1 was the one who first investigated the photoionization cross-section of hydrogenic impurities in bulk semiconductors. Photon energy depended photoionization cross section has been studied earlier for bulk semiconductors, 2 quantum wells, 3 4 quantum well wires [5][6][7] and quantum dots. 8 9 In all the studies they found that the photoionization cross section depended upon the * Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%